Results of early intervention in the baby with cerebral motor disturbance - S. H. Irwin-Carruthers (AOSIS, 1981)
The results of a study comparing the early and late treatment of babies with cerebral motor disturbance are discussed. Criteria for diagnosis must be established before tests can begin. It would appear that early intervention results in marked improvement but more surveys are necessary to provide convincing evidence.